AuditRRAS-APS: validation of an instrument for Self-Assessment in Primary Health Care - Barbosa, Adriana Aparecida de Oliveira; Detregiachi, Cláudia Rucco Penteado; Oliveira, Maria Rita Marques de (FapUNIFESP (SciELO), 2025)
Abstract Objective To construct and validate an instrument for the self-assessment of actions related to the care of chronic health conditions and their associated risk factors. Methods This is a methodological study structured in five stages: (1) definition of the conceptual framework, based on a previous instrument; (2) construction of items and response scales, with an exploratory literature review and analysis of the official Ministry of Health documents, incorporating specific guidelines; (3) selection and organization of items, refining criteria and domains, consulting internal experts; (4) structuring of the initial version of the instrument, ensuring clarity and relevance of the items; and (5) content validation through the Nominal Group Technique, conducted in two rounds with the participation of academic and technical experts from the state and federal levels. A guidance manual for the practical application of the instrument was also developed. Results The development and validation of AuditRRAS-APS involved the three main researchers and 20 experts (five internal and 14 ad hoc). The final version of AuditRRAS-APS has 173 items organized into five dimensions: 1) Organization of Comprehensive Care in Primary Health Care; 2) Organization and management of Primary Health Care; 3) Institutionalization of public policies for chronic conditions and their risk factors; 4) Social participation; and 5) Self-perception of the performance of the Unified Health System. Conclusion Despite its length, AuditRRAS-APS was well evaluated, showing that the approach used in its elaboration was comprehensive enough to meet the expectations of the experts. RESUMO Objetivo Construir e validar um instrumento para a autoavaliação das ações relacionadas ao cuidado das condições crônicas de saúde e seus fatores de risco associados. Métodos Trata-se de um estudo do tipo metodológico estruturado em cinco etapas: 1) definição da estrutura conceitual, com base em um instrumento prévio; 2) construção dos itens e escalas de resposta, com revisão exploratória da literatura e análise de documentos oficiais do Ministério da Saúde, incorporando diretrizes específicas; 3) seleção e organização dos itens, refinando critérios e domínios, consultando especialistas internos; 4) estruturação da versão inicial do instrumento, garantindo clareza e relevância dos itens; e 5) validação de conteúdo por meio da Técnica de Grupo Nominal, realizada em duas rodadas com a participação de especialistas acadêmicos e técnicos do âmbito estadual e federal. Também foi desenvolvido um manual orientador para a aplicação prática do instrumento. Resultados O desenvolvimento e validação do AuditRRAS-APS envolveu as três pesquisadoras principais e 20 especialistas (sendo cinco internos e 14 ad hoc). A versão final do AuditRRAS-APS possui 173 itens organizados em cinco dimensões: 1) Organização do Cuidado Integral na Atenção Primária à Saúde; 2) Organização e gestão da Atenção Primária à Saúde; 3) Institucionalização das políticas públicas para condições crônicas e seus fatores de riscos; 4) Participação social; e 5) Autopercepção do desempenho do Sistema Único de Saúde. Conclusão Apesar de sua extensão, o AuditRRAS-APS foi bem avaliado, mostrando que a abordagem empregada na sua elaboração foi abrangente o bastante para satisfazer as expectativas dos especialistas.